Controversial Aspects of the Internal Control Concept - A. V. Bоdуako (Учёт. Анализ. Аудит, 2018)
The logic of the paper is based on defining the key aspects of internal control notion as a phenomenon in modern management process. The article considers the issues of applying Article 19 “Internal control” of the Federal Act 402 taking into consideration the progress in microelectronics, information technology and telecommunications and their relation to control. It also discusses the important aspects of “The Conceptual Framework of Risk Management in Organizations” related to the issues of internal control as a wider notion of risk management. It is also noted that this document doesn’t cancel “The Conceptual Framework of Internal Control” but include it as an integrant part.The author draws the attention to the modern transformation of methodological views on internal control organization particularly to the shift of emphasis with regard to identification and elimination of risks. Nowadays it is believed that the management task is to make decisions about the level of uncertainty which the organization is prepared to accept seeking to increase value for stakeholders.The author concludes that the system of internal corporate control (SICC) is a multilevel process, the subjects of which are all company’s management bodies, departments, divisions and their employees whose activity is related to risks able to influence the company’s goals achievement including such an important goal as reliable presentation of company’s activity results in financial and other types of reporting.The article contains the proposals on the content of risk-oriented internal corporate control. Sustainability of an enterprise is based on getting right economic strategy which means that the goals should be set in a way that ensures the optimal balance between the technological development and growth (scaling) of the company, its profitability and risks along with thrift and efficient use of resources available.